The effects of daily gratitude writing and self-paced high intensity interval training on regulating emotional distress, sustained attention and hedonic perception among students in Universiti Sains Malaysia, Health Campus - Sivapragasam, Kavitha A/P (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
A 2017’s cross-sectional study found that more than 80% of 287 Malaysian adolescents were either, depressed, stressed or experiencing anxiety with university students have being identified as the higher risk group for developing those mental health challenges. Due to the transitional phase adolescents face, there has been inadequate coping strategies towards stress. However, positive psychology has highlighted the potential impact that physical activities and the act of expressing gratitude has towards managing psychological challenges. Hence, this study aims to determine the effects of daily gratitude writing and self-paced high intensity interval (HIIT) training towards regulating emotional distress, sustained attention and hedonic perception among 46 students in Universiti Sains Malaysia, Health Campus. The selfdetermination theory and the ‘Broaden-and-Build’ theory of positive emotions contributed significantly to the development of this study. The RESET app – a mobile application was introduced as a gratitude journaling tool while quantitative data was obtained through the administration of a pre-post-Depression, Anxiety and Stress Scale-21 Questionnaire (DASS-21), Borg’s Scale for Rate of Perceived Exertion (RPE), Feeling Scale, and the Digital Vigilance Test (DVT). Upon completing the 8-week study, the results showed that there were differences between the pre-post intervention for DASS-21 and RPE scores within the 4 experimental groups but the results were not significant (p > .050). However, there was a significant decrease in errors made in the DVT (F (1,42) = 17.057, p = .000) while there was a significant increase in the Feeling Scale scores for gratitude journaling within participants (F (2,40) = 3.879, p = .029). Due to the study’s novelty, the results serve as a launch pad for future works in the efforts of integrating physical activities and positive psychology interventions towards effective psychological management and nurturing among the Malaysian youth.